Stereographic for Development of Stricture Pattern of Geological Alteration Zone in Atauro Island, Timor-Leste - Gomes, Nazario; Sutarto, Sutarto; Soesilo, Joko; Purwanto, Heru Sigit; Christophe, James (Asian Journal of Social and Humanities, 2024)
The geological structural patterns and hydrothermal alteration zones of Atauro Island, Timor-Leste, which are influenced by the collision mechanism between the Banda Arc and the Australian Continent, are the subject of this study. The study identifies fault types and alteration zones through stereographic analysis. It indicates the possibility of mineralization in the area. Four alteration zones were identified in this study: argillic, Propylitic, calcosite, and geotite. The analysis results show that left-striking and normal faulting were essential in forming these zones. The mineralization zones, mainly chalcopyrite and chalcocite, are related to the north-northeast trending left horizontal Fault. In addition, this study suggests additional research that includes mineralogy, geochemical, and geophysical analyses to understand more about the characteristics of hydrothermal alteration zones and possible mineralization on Atauro Island. The results of this study are expected to improve our understanding of mineral resources in the region, and it is suggested that this information be considered by authorities responsible for the management of potential natural resources on Atauro Island, Timor.